Antibacterial effects of Oradex, Gengigel and Salviathymol-n mouthwash on dental biofilm bacteria - Al-Bayaty, F.H.; Taiyeb-Ali, T.B.; Abdulla, M.A.; Mahmud, Z.B. (2011)
Three mouthwashes Gengigel, Oradex and Salviathymol N, were tested using experimental microorganisms included Fusobacterium nucleatum, Streptococcus mitis, Streptococcus constellatus, Eikenella corrodens and dental plaque. Staphylococcus aureus and Escherichia coli were used as internal controls. Antibacterial activity was done by diffusion test. Minimum inhibitory concentration test and assessment of bacterial morphology was carried out using scanning electron microscopy (SEM). Results showed that Oradex had a higher antibacterial effect, followed by Salviathymol N; Gengigel mouthwash have weak antibacterial effects against tested microorganisms and dental plaque. SEM observations demonstrated that chlorhexidine exhibited obvious changes in that most of the bacteria loss their original shape and became irregular. The cell also shrunk, became reduced in size. Salviathymol N showed some significant changes while Gengigel failed to exhibited changes on the bacterial morphology of the tested microorganisms. In conclusion Oradex and Salviathymol N can be used as antibacterial mouthwash for chemical plaque control. Gengigel demonstrated weak antibacterial effects which could not be recommended as anti-dental plaque agent.